An Examination of Academic Procrastination Levels among Undergraduate Kuwait University Students and their Effect on some Demographic Variables. - Djilali BOUHMAMA (Revue des Sciences Humaines)
The present research is aimed to investigate the academic procrastination levels among undergraduate Kuwait University students and to explore the effect of some demographic variables namely gender, and academic achievement. The sample consisted of 300 students (150 males and 150 females) from the college of education, Kuwait University. They ranged in age from 18 to 27 (M = 19.51, SD= 1.77)